ORA and the Oxford Common Filesystem Layer (OCFL) in Fedora 6 - Wrobel, T (2023)
A one-page report describing ORA's plans to use the Oxford Common Filesystem Layer (OCFL) in Fedora 6 as part of its digital presentation solution. This paper was part of a presentation to Code4Lib 2023 made by Arran Griffith and Stefano Cossu.